Do mergers and acquisitions increase default risk? Evidence from the European market - Wolfgang Bessler; Hidde Steenbeek; Wim Westerman (The Central European Review of Economics and Management (CEREM), 2019)
Aim: In this study, we examine the changes in default risk of the bidder over the course of a merger or acquisition. The data set consists of 531 deals in which the acquirers are European firms. We employ a general set of determinants to analyse the change in default risk and extend the literature by providing new empirical evidence for the European capital market. Research design: Abnormal returns are analysed to provide preliminary insights into the merger induced valuation effects. All hypothesized relationships on the changes in default risk are tested via a regression analysis. We differentiate these results further by analysing which factors determine the increase in default risk. Findings: Previous research on this issue reported mixed results. The main finding of our empirical analysis is that, on average, mergers and acquisitions of European bidders significantly increase default risk during the post-merger period. Originality: This study adds to the mergers and acquisitions literature for European bidders and targets. The empirical findings suggest that some observed relationships and determinants are different in Europe than in the United States. Implications: This research introduces a default risk model that could be applied to predict bidder performance subsequent to a merger or acquisition by analysing possible changes in default risk of the bidder. It also provides some possible explanations for the average increase in default risk. This study may help practitioners to better assess the potential risks when acquiring other firms. Key words: mergers & acquisitions, abnormal returns, default risk, Europe JEL Codes: G32, G34
Keywords: 330